NSGA-II Algorithm for Assembly Line Balancing with Multi-Resource Constraints - M. F. F., Ab Rashid; M. M., Razali; Make, M. R. Abdullah; N. M. Zuki, N. M.; A. N. M., Rose (2016)
The existing line balancing algorithm assume that any assembly task can be performed in any workstation. However, in reality, there are resource constraints to be considered such as machine, tool, skilled worker etc. In this research we consider all the resources in assembly, so that the assembly task assignment can be performed smoothly using the available resources in the manufacturing plant. In this research, we developed an Elitist Non-Dominated Sorting Genetic Algorithm (NSGA-II) to optimize assembly line balancing with resource constraint (ALB-RC).